Central American Free Trade Agreement-Dominican Republic (CAFTA-DR): What's in It for Florida Agriculture? - Edward A. Evans (EDIS)
The purpose of this article is to summarize the main elements of the Central American Free Trade Agreement-Dominican Republic (CAFTA-DR), and to take a closer look at the Agreement to see what is in it for Florida producers.  This is EDIS document FE564, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published June 2005.